Manner of death [compact disc, unabridged] - Cook, Robin, 1940- (Jack Stapleton and Laurie Montgomery, 2023)
New York City's chief medical examiner, Laurie Montgomery, ignores her own professional rules to investigate the suspicious death of a colleague. It's a dangerous inquiry that might cost Laurie her life.